Social Capital in Japanese and Finnish Business Relationships - A Comparative Study - Jääskeläinen, Joonatan (My University, 2011)
Concepts of social capital and embeddednes have established a firm position in modern studies of business administration. As classic theories of economy, they can be utilized to study social aspects in business relationships. This hermeneutic study focuses on researching matters of social capital and embeddednes in business relationships in Japan and Finland. Social constructs of business relationships vary according to cultural influence they are exposed – the aim of this paper is to compare the similarities and differences of these influences within the context of Japanese and Finnish culture, as well as to present the practical manifestations of social capital in the two countries. The theoretical framework provided in the paper defines major theories and arguments of the literature related to issues of social capital and embeddednes and in addition, essential previous findings which may concern this study. This paper also includes an empirical, qualitative semi-structured interview study. Six Finnish informants from varying industries with extensive experience on Japanese and Finnish culture and business were interviewed. The informants shared their observations and opinions on the differences and similarities in Japanese and Finnish business relationships. The results of the empirical study imply the importance of cultural influence especially in the case of Japan. Some similarities of social aspects between the countries can be found, but largely, the differences (imposed by the national culture or international business trends) prove to be substantial.
Keywords: Social capital; embeddednes; Japanese business relationships; Finnish business relationships; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|